Efektivitas Teknik Progrressive Muscle Relation Training (PMRT) dalam Mengurangi Disappointment Level pada Lansia di Panti Sosial Lanjut Usia Harapan Kita Kota Palembang - Opia Sari, Nabilla; Razzaq, Abdur; Utami Fitri, Hartika (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research examines the "Effectiveness of Progressive Muscle Relation Training (PMRT) Techniques in Reducing Disappointment Levels in the Elderly at the Harapan Kita Social Institution for the Elderly in Palembang City". This research aims to find out first, the level of Disappointment Level in the elderly before going to the Social Institution, and second, research on the effectiveness of the Progressive Muscle Relation Training (PMRT) technique in reducing Disappointment Level in the elderly at the Harapan Kita Social Institution for the Elderly in Palembang City. This study uses a descriptive quantitative approach, with a population of 22 people with a sample of 12 people using probability sampling. Data collection techniques using questionnaires, observation and documentation. Data analysis techniques through the Wilxocon test with the help of the SPSS version 23 window form program. The results showed first, the level of Disappointment Level for the elderly at the Harapan Kita Social Institution in Palembang City was in the High category. Second, the results show that Asymp.sig (2-tailed) has a value of .002. The value of .002 <0.05, it can be concluded that Ha is accepted and H0 is rejected, which means that group counseling with the Progressive Muscle Relation Training (PMRT) technique is effective in reducing the Disappointment Level in the elderly at the Harapan Kita Social Institution for the Elderly, Palembang City.